(untitled) (Revista Cocar, 2013)
Circula hoje na área de ensino/aprendizagem o discurso da necessidade de se ter como objetivo o desenvolvimento de um sujeito crítico em sala de aula. Pretendemos, baseando-nos em alguns autores como Bakhtin, Morin, entre outros, examinar o que significa ser crítico nos discursos de graduandos em Letras e de formandos do Curso Normal. Entendemos que esses discursos são prerrogativas de ações e desvelam possíveis realidades que são/serão observadas na atualidade. Palavras-chave: ensino, discurso, sujeito crítico. what is to be critical, after all? d responsibility and act in education Now circulates in the area of teaching / learning of speech need to be aimed at the development of a critical subject in the classroom. We intend, basing ourselves in some authors such as Bakhtin, Morin, among others, examine what it means to be critical in the discourse of undergraduate students in Arts and the Teacher Training Course. We believe that these speeches are prerogatives of actions and reveal possible realities that are / will be observed today. Keywords: Education, discourse, critical subject. " "